Expert System of Quail Disease Diagnosis using Forward Chaining Method - B. Herawan Hayadi; Kasman Rukun; Rizky Ema Wulansari; Tutut Herawan; Dahliyusmanto Dahliyusmanto; David Setaiwan; Safril Safril (Institute of Advanced Engineering and Science, 2017)
Expert system applications were in great demand in various circles since 1950, with a coverage area that was large. Expert System on the organization was aimed at adding value, increasing productivity as well as the area of managerial can make decisions quickly and accurately. Neither with organizations that did business quail, which was very promising, but needed to be alert for the presence of disease in quail healthy, as in the case in birds quail were highly vulnerable to various kinds of diseases caused by viruses or bacteria. the benefits of the expert system that was able to diagnose quickly and accurately to the symptoms of the disease caused was expected to helped the farmers in of anticipation the many losses caused by disease. Required accuracy and the accuracy of the counting in diagnosing the symptoms of the disease in order to summarized the results by using forward chaining method.